MANAJEMEN PEMBERDAYAAN GURU DALAM MENINGKATKAN KOMPETENSI PROFESIONAL OLEH KEPALA SEKOLAH DI SMPN 1 SAMBAS. - Ayu Kartika; Usman Radiana; Sukmawati Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the management of teacher empowerment in improving professional competence by principals at SMPN 1 Sambas. This form of research used a qualitative approach. The research subjects were 8 people with the criteria of principals, vice principals, teachers. Research subjects through purposive sampling. Descriptive research method with observation, interviews, documentation. Data collection tools in the form of observation sheets, interview guidelines, documents. Data analysis used reduction, presentation, verification. The main findings of the study: planning was carried out by analyzing teacher profiles considering the requirements for participating in teacher empowerment, coordination carried out by school principals on the sidelines to determine the development of teacher professional competence empowerment, directives were carried out through sharing, providing motivation, and direct orders to participate in teacher professional competence empowerment activities, evaluation is done by reviewing weekly reports by the teacher, analyzing and providing follow-up. The conclusion of this study in the form of planning, coordination, direction, and evaluation of teacher empowerment went quite well. The implication of this research is that with the management of teacher professional competence empowerment, it is hoped that teachers can pay attention to their competence to the maximum